Symptoms of the self : tuberculosis and the making of the modern stage - Barker, Roberta (Studies in theatre history and culture, 2022)
"Symptoms of the Self offers the first full study of one of the most paradoxically popular figures in transatlantic theatre history : the stage consumptive. Consumption, or tuberculosis, remains one of the world's most deadly epidemic diseases; in the nineteenth and early twentieth centuries in France, Britain, and North America, it was a leading killer, responsible for the deaths of as many as one in four members of the population. Despite-or perhaps because of-their horrific experiences of tubercular mortality, throughout the nineteenth and well into the twentieth century audiences in these same countries flocked to see consumptive characters love, suffer, and die onstage. Beginning with the origins of the stage consumptive in Romantic-era France and ranging through to the queer theatres of New York City in the 1970s, this book explores famous plays such as La dame aux camélias (Camille) and Uncle Tom's Cabin alongside rediscovered sentimental dramas, frontier melodramas, and naturalistic problem plays. It shows how theatre artists used the symptoms of tuberculosis to perform the inward emotions and experiences of the modern self, and how the new theatrical vocabulary of realism emerged out of the innovations of the sentimental stage. In the theatre, the consumptive character became a vehicle through which-for better and for worse-standards of health, beauty, and virtue were imposed; constructions of class, gender, and sexuality were debated; the boundaries of nationhood were transgressed or maintained; and an exceedingly fragile whiteness was held up as a dominant social ideal. By telling the story of tuberculosis on the transatlantic stage, Symptoms of the Self aims to uncover some of the wellsprings of modern Western theatrical practice-and of ideas about the self that still affect the way human beings live and die"--